Modified asphalt waterproof coiled material and preparation method thereof
By designing a combination of aging-resistant and adhesive layers in modified bitumen waterproof membranes, and utilizing specific components and processes, the problems of insufficient durability, heat resistance, and workability of modified bitumen waterproof membranes have been solved. This has resulted in rapid cross-linking, excellent bonding strength, and thermal aging performance, meeting the high-efficiency requirements of membrane production.
Patent Information
- Application Number
- CN202511798661.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-02
- Publication Date
- 2026-02-06
AI Technical Summary
Existing modified bitumen waterproof membranes have shortcomings in terms of durability, heat resistance, and workability, especially in terms of decreased low-temperature flexibility, insufficient peel strength, and mismatched production efficiency after long-term thermo-oxidative aging.
The structure adopts an aging-resistant layer and an adhesive layer. The aging-resistant layer includes a polyester base and a cross-linked modified asphalt coating, while the adhesive layer is a non-cross-linked modified asphalt coating. Rapid cross-linking and high bonding strength are achieved through a combination of 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder and cross-linking agent in a specific ratio.
It achieves rapid crosslinking (≤2h), high bonding strength (peel strength ≥1.8N/mm) and excellent thermal aging performance, reduces mass loss after thermal aging, improves the heat resistance and low-temperature flexibility of the roll material, and meets the high-efficiency requirements of roll material production.
Smart Images

Figure CN121473149A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building waterproofing materials technology, and in particular to a modified bitumen waterproof membrane and its preparation method. Background Technology
[0002] Traditional thermoplastic styrene-butadiene rubber (SBS) modified bitumen waterproof membranes are mainly modified through physical blending, which results in insufficient durability. The physically cross-linked SBS network is prone to degradation after long-term thermo-oxidative aging, leading to decreased low-temperature flexibility; at the same time, the mass loss after heat aging is relatively high. In addition, the poor heat resistance poses a risk of slippage failure in extreme high-temperature weather.
[0003] The method of improving the performance of modified asphalt through chemical cross-linking has construction defects when applied to roofing membranes. The main problems are reduced fluidity of the chemically cross-linked modified asphalt and insufficient oil output during hot-melt application (actual measurements show that poor adhesion due to heat treatment with a spray gun results in a peel strength of only 1.0~1.5 N / mm), failing to meet the 1.5 N / mm requirement of GB / T 18242-2008.
[0004] Furthermore, the application of chemical crosslinking in modified bitumen for waterproof membranes presents a mismatch in production efficiency. Common chemical crosslinking agent formulations require a development time of more than 3 hours, which cannot match the pace of continuous production lines for bitumen membranes (production line speeds are typically required to be ≤2 hours / batch).
[0005] Some roll material applications use a sulfur / accelerator DTDM crosslinking system, but this does not resolve the conflict between crosslinking speed and workability. Other roll material designs improve adhesion by adding a transition layer, but do not optimize the aging resistance of the crosslinking network.
[0006] Currently, there is no comprehensive solution in the industry that simultaneously achieves "rapid cross-linking (≤2h) + high adhesion (peel strength ≥1.8N / mm) + long life (heat resistance of roll material and low-temperature flexibility without cracking after thermal aging)". Summary of the Invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a modified bitumen waterproof membrane and its preparation method. The modified bitumen waterproof membrane provided by the present invention can be rapidly cross-linked and has superior bonding peel strength and thermal aging performance.
[0008] This invention provides a modified bitumen waterproof membrane, comprising: an aging-resistant layer; and an adhesive layer formed on the aging-resistant layer;
[0009] The aging-resistant layer comprises: a polyester base; and a cross-linked modified bitumen coating formed on the outer surface of the polyester base;
[0010] The adhesive layer is a non-crosslinked modified asphalt coating;
[0011] The cross-linked modified asphalt coating is prepared from raw materials including 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and cross-linking agent;
[0012] The non-crosslinked modified asphalt coating is prepared from raw materials including 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder.
[0013] Preferably, the crosslinking agent comprises:
[0014] Insoluble sulfur 15 wt%~25 wt%;
[0015] Ultra-fast accelerator 4 wt%~8 wt%;
[0016] Acceleration accelerator 6 wt%~12 wt%;
[0017] Medium-speed accelerator 8 wt%~12 wt%;
[0018] Nano zinc oxide 55 wt%~65 wt%;
[0019] The sum of the amounts of the components is 100%.
[0020] Preferably, the ultra-high speed accelerator is BZ and / or EZ;
[0021] The speed-up accelerator is TMTD and / or TMTM;
[0022] The medium-speed accelerator is at least one of M, DM and CZ;
[0023] The particle size of the nano zinc oxide is 50~100 nm.
[0024] Preferably, in the raw materials for preparing the crosslinked modified asphalt coating, the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and crosslinking agent is 20~35: 20~35: 1.5~3: 12~18: 20~35: 0.05~0.15.
[0025] Preferably, the method for preparing the crosslinked modified asphalt includes the following steps:
[0026] 70# asphalt and 200# asphalt are heated and melted to 175~180℃, SBS is added, and the mixture is sheared at 3500~4500 r / min and 180~185℃. Then, a crosslinking agent is added, and the mixture is heated to 185~190℃ and stirred at 300~500 r / min. Waste tire powder is added and stirred, and then stone powder is added and stirred to obtain crosslinked modified asphalt.
[0027] Preferably, the thickness of the aging-resistant layer is 2 to 3.5 mm.
[0028] Preferably, in the raw materials for preparing the non-crosslinked modified asphalt coating, the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder is 20~35:20~35:1.5~3:12~18:20~35.
[0029] Preferably, the method for preparing the non-crosslinked modified asphalt includes the following steps:
[0030] 70# asphalt and 200# asphalt are heated and melted to 175~180℃, SBS is added, and the mixture is sheared at 3500~4500 r / min and 180~185℃. Waste tire powder is then added, and the mixture is heated to 185~190℃ and stirred at 300~500 r / min. Stone powder is then added and stirred to obtain non-crosslinked modified asphalt.
[0031] Preferably, the thickness of the non-crosslinked modified asphalt layer is 0.5~1 mm;
[0032] The thickness of the modified bitumen waterproof membrane is 3-4 mm.
[0033] This invention provides a method for preparing the modified bitumen waterproof membrane described above, comprising the following steps:
[0034] A cross-linked modified asphalt is coated on both sides of a polyester base, and after curing, an aging-resistant layer is obtained.
[0035] A non-crosslinked modified bitumen is coated on one side of the aging-resistant layer, and after curing, an adhesive layer is obtained; thus, a modified bitumen waterproof membrane is obtained.
[0036] The modified bitumen waterproof membrane provided by this invention can quickly crosslink, and the crosslinking time (development time, i.e., the stirring time after adding the crosslinking agent and the stirring time after adding waste tire powder in the preparation method of crosslinked modified bitumen, excluding the stirring time after adding stone powder) can be ≤2h; the bond peel strength is better, with a peel strength ≥1.8N / mm; the thermal aging performance is better, with a mass loss <0.4% after thermal aging. Attached Figure Description
[0037] Figure 1 A schematic diagram of the structure of a modified bitumen waterproof membrane provided in one embodiment of the present invention;
[0038] Figure 2 This is a fluorescence microscope image of the crosslinking effect of asphalt samples developed for 2 hours in the experimental group of Example 1 of the present invention;
[0039] Figure 3 This is a fluorescence microscopy crosslinking effect image of an asphalt sample developed for 2 hours in the control group of Example 1 of the present invention;
[0040] Figure 4 This is a fluorescence microscopy crosslinking effect image of an asphalt sample from the control group of Example 1 of the present invention after 4 hours of development;
[0041] Figure 5 This is a fluorescence microscope image of the crosslinking effect of asphalt samples developed for 1.5 hours in the experimental group of Example 2 of the present invention;
[0042] Figure 6 This is a fluorescence microscopy crosslinking effect image of an asphalt sample developed for 1.5 hours in the control group of Example 2 of the present invention;
[0043] Figure 7 This is a fluorescence microscopy crosslinking effect image of an asphalt sample developed for 3.5 hours in the control group of Example 2 of the present invention. Detailed Implementation
[0044] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0045] This invention provides a modified bitumen waterproof membrane, comprising: an aging-resistant layer; and an adhesive layer formed on the aging-resistant layer;
[0046] The aging-resistant layer comprises: a polyester base; and a cross-linked modified bitumen coating formed on the outer surface of the polyester base;
[0047] The adhesive layer is a non-crosslinked modified asphalt coating;
[0048] The crosslinked modified asphalt coating is prepared from raw materials including 70# asphalt (70# asphalt), 200# asphalt (200# asphalt), SBS, waste tire powder, stone powder and crosslinking agent;
[0049] The non-crosslinked modified asphalt coating is prepared from raw materials including 70# asphalt (70# asphalt), 200# asphalt (200# asphalt), SBS, waste tire powder and stone powder.
[0050] In some embodiments of the present invention, the aging-resistant layer comprises: a polyester base; a first crosslinked modified bitumen coating formed on the upper surface of the polyester base; and a second crosslinked modified bitumen coating formed on the lower surface of the polyester base.
[0051] Figure 1 This is a schematic diagram of the structure of a modified bitumen waterproof membrane provided in one embodiment of the present invention. Wherein, 1 is an aging-resistant layer, 1-1 is a first cross-linked modified bitumen coating, 1-3 is a second cross-linked modified bitumen coating, 1-2 is a polyester base, and 2 is an adhesive layer.
[0052] In some embodiments of the present invention, the crosslinking agent comprises:
[0053] Insoluble sulfur 15 wt%~25 wt%;
[0054] Ultra-fast accelerator 4 wt%~8 wt%;
[0055] Acceleration accelerator 6 wt%~12 wt%;
[0056] Medium-speed accelerator 8 wt%~12 wt%;
[0057] Nano zinc oxide 55 wt%~65 wt%;
[0058] The sum of the amounts of the components is 100%.
[0059] In this invention, the insoluble sulfur is the crosslinking host.
[0060] The ultra-high-speed accelerator serves to initiate crosslinking. The ultra-high-speed accelerator is BZ and / or EZ.
[0061] The function of the ultra-fast accelerator is to accelerate the reaction. The ultra-fast accelerator is TMTD and / or TMTM.
[0062] The function of the medium-speed promoter is to stabilize the network. The medium-speed promoter is at least one of M, DM, and CZ.
[0063] The nano-zinc oxide acts as an activator. The particle size of the nano-zinc oxide is 50~100 nm.
[0064] The present invention does not impose any special restrictions on the preparation method of the crosslinking agent. The crosslinking agent can be obtained by mixing insoluble sulfur, ultra-high-speed accelerator, high-speed accelerator, medium-speed accelerator and nano zinc oxide.
[0065] Regarding cross-linked modified bitumen coatings:
[0066] In some embodiments of the present invention, the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and crosslinking agent in the raw materials for preparing the crosslinked modified asphalt coating is 20~35:20~35:1.5~3:12~18:20~35:0.05~0.15, for example 25:30:2.5:16:26.4:0.1, 26:29:2:17:25.92:0.08.
[0067] The SBS in question is grade 791H SBS.
[0068] The particle size of the waste tire powder is 60 mesh.
[0069] The stone powder has a particle size of 200 mesh.
[0070] In some embodiments of the present invention, the method for preparing the crosslinked modified asphalt includes the following steps:
[0071] 70# asphalt and 200# asphalt are heated and melted to 175~180℃, SBS is added, and the mixture is sheared at 3500~4500 r / min and 180~185℃. Then, a crosslinking agent is added, and the mixture is heated to 185~190℃ and stirred at 300~500 r / min. Waste tire powder is added and stirred, and then stone powder is added and stirred to obtain crosslinked modified asphalt.
[0072] The heating rate to 175~180℃ is 10~20℃ / min, for example, 15℃ / min or 18℃ / min.
[0073] The shearing time is 35-45 minutes, for example, 40 minutes. The shearing speed can be 4000 r / min, and the temperature can be 182℃. The shearing is performed using a shearing machine.
[0074] The heating rate to 185~190℃ is 5~10℃ / min, for example, 5℃ / min or 8℃ / min.
[0075] The stirring time at 185~190℃ and 300~500 r / min is 5~15 min, for example, 10 min. The stirring temperature when adding the crosslinking agent can be 188℃; the stirring rate can be 400 r / min.
[0076] The temperature for adding waste tire powder and stirring is 185~190℃, for example, 188℃; the time is 1.3~1.7 h, for example, 1.5 h. The stirring rate for adding waste tire powder is the same as the stirring rate for adding crosslinking agent.
[0077] When adding stone powder, the stirring temperature should be 185~190℃, for example, 188℃; the stirring time should be 20~45 min, for example, 20 min. The stirring rate when adding stone powder should be the same as the stirring rate when adding crosslinking agent.
[0078] In some embodiments of the present invention, the thickness of the first cross-linked modified asphalt layer is 0.5~1.25 mm, for example, 1 mm or 1.25 mm. The thickness of the second cross-linked modified asphalt layer is 0.5~1.25 mm, for example, 1 mm or 1.25 mm.
[0079] In some embodiments of the present invention, the thickness of the aging-resistant layer is 2 to 3.5 mm, such as 3 mm or 3.5 mm.
[0080] Regarding non-crosslinked modified bitumen coatings:
[0081] In some embodiments of the present invention, the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder in the raw materials for preparing the non-crosslinked modified asphalt coating is 20~35:20~35:1.5~3:12~18:20~35, for example 25:30:2.5:16:26.5 or 26:29:2:17:26.
[0082] The SBS in question is grade 791H SBS.
[0083] The particle size of the waste tire powder is 60 mesh.
[0084] The stone powder has a particle size of 200 mesh.
[0085] In some embodiments of the present invention, the method for preparing the non-crosslinked modified asphalt includes the following steps:
[0086] 70# asphalt and 200# asphalt are heated and melted to 175~180℃, SBS is added, and the mixture is sheared at 3500~4500 r / min and 180~185℃. Waste tire powder is then added, and the mixture is heated to 185~190℃ and stirred at 300~500 r / min. Stone powder is then added and stirred to obtain non-crosslinked modified asphalt.
[0087] The heating rate to 175~180℃ is 10~20℃ / min, for example 15℃ / min or 18℃ / min.
[0088] The shearing time is 35-45 minutes, for example, 40 minutes. The shearing speed can be 4000 r / min, and the temperature can be 182℃. The shearing is performed using a shearing machine.
[0089] The heating rate to 185~190℃ is 5~10℃ / min, for example, 5℃ / min or 8℃ / min.
[0090] The stirring time at 185~190℃ and 300~500 r / min is 1.3~1.7 h, for example 1.5 h.
[0091] The temperature at which waste tire powder is added and stirred can be 188℃; the stirring speed can be 400 r / min.
[0092] When adding stone powder, the stirring temperature should be 185~190℃, for example, 188℃; the stirring time should be 20~45 min, for example, 20 min. The stirring rate of adding stone powder should be the same as the stirring rate of adding waste tire powder.
[0093] In some embodiments of the present invention, the adhesive layer is formed on one side of the aging-resistant layer.
[0094] In some embodiments of the present invention, the thickness of the non-crosslinked modified asphalt layer is 0.5~1 mm, for example 1 mm or 0.5 mm.
[0095] In some embodiments of the present invention, the thickness of the modified bitumen waterproof membrane is 3 to 4 mm, for example, 4 mm.
[0096] This invention also provides a method for preparing the modified bitumen waterproof membrane described above, comprising the following steps:
[0097] A cross-linked modified asphalt is coated on both sides of a polyester base, and after curing, an aging-resistant layer is obtained.
[0098] Non-crosslinked modified bitumen is coated on one side of the aging-resistant layer (the bottom surface of the hot-melt construction), and after curing, an adhesive layer is obtained; thus, a modified bitumen waterproof membrane is obtained.
[0099] In some embodiments of the present invention, the cross-linked modified bitumen coated on both sides of the polyester base has the same thickness.
[0100] In some embodiments of the present invention, cross-linked modified asphalt is coated on both sides of a polyester base, and after curing, an aging-resistant layer is obtained, comprising:
[0101] A first cross-linked modified asphalt coating is obtained by coating the upper surface of a polyester base with cross-linked modified asphalt and curing it; a second cross-linked modified asphalt coating is obtained by coating the lower surface of a polyester base with cross-linked modified asphalt and curing it.
[0102] The present invention does not impose any special restrictions on the source of the raw materials used above, and they can be commercially available.
[0103] Beneficial effects:
[0104] Improved durability: The cross-linked network reduces the mass loss rate after thermal aging from over 0.5% to below 0.4%, and the material exhibits low-temperature flexibility without cracking during thermal aging, with a brittle fracture temperature more than 1.0℃ lower than the non-cross-linked temperature; the heat resistance is improved compared to the slip temperature of traditional non-cross-linked modified bitumen rolls (tested in GB 18242-2008).
[0105] Construction adaptability: The lower layer of non-crosslinked asphalt increases the oil yield by 40% compared to crosslinked modified asphalt, and the peel strength is ≥1.8N / mm;
[0106] Production efficiency: The cross-linking time has been shortened from 3 hours to 1.5 hours, improving efficiency and making it more suitable for the production rhythm of roll materials.
[0107] To further illustrate the present invention, the following detailed description of a modified bitumen waterproof membrane and its preparation method provided by the present invention is provided in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0108] Example 1
[0109] Crosslinking agent include:
[0110] Insoluble sulfur 18 wt%
[0111] Ultra-fast acceleration accelerator EZ 5 wt%
[0112] Acceleration accelerator TMTD 7 wt%
[0113] Medium-speed accelerator DM 10 wt%
[0114] Nano zinc oxide 60 wt%.
[0115] The particle size of the nano zinc oxide is 50~100 nm.
[0116] Rapid crosslinking verification
[0117] The asphalt samples for the experimental group were prepared using 70# asphalt, 200# asphalt, SBS and crosslinking agent as raw materials; the mass ratio of 70# asphalt, 200# asphalt, SBS and crosslinking agent was 50:50:5.5:0.18.
[0118] Preparation method: Heat 70# asphalt and 200# asphalt to melt and heat to 180℃ (heating rate is 10℃ / min). Add SBS and shear at 183℃ for 40 min at 4000 r / min. Then add crosslinking agent and heat to 188℃ at 400 r / min for 2 h and 4 h. Take asphalt samples from the experimental group to observe the crosslinking development.
[0119] Control group asphalt samples: The crosslinking agent in the experimental group asphalt samples was replaced with sulfur, while the remaining raw materials and procedures were the same as those in the experimental group. The crosslinking development was observed in the control group asphalt samples.
[0120] Figure 2 This is a fluorescence microscope image of the crosslinking effect of asphalt samples developed for 2 hours in the experimental group of Example 1 of the present invention.
[0121] Figure 3 This is a fluorescence microscopy crosslinking effect image of an asphalt sample developed for 2 hours in the control group of Example 1 of the present invention.
[0122] Figure 4 This is a fluorescence microscope image of the crosslinking effect of an asphalt sample developed for 4 hours in the control group of Example 1 of the present invention.
[0123] from Figures 2-4 It can be seen that the experimental group obtained by using the crosslinking agent of the present invention can achieve the same fluorescent crosslinking state as the control group after 4 hours of development after 2 hours.
[0124] Crosslinked modified bitumen coating It is prepared from raw materials including 70# asphalt, 200# asphalt, SBS (791H grade), waste tire powder (60 mesh), stone powder (200 mesh) and the crosslinking agent; the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and crosslinking agent is 25:30:2.5:16:26.4:0.1.
[0125] The preparation method of the crosslinked modified asphalt includes the following steps:
[0126] 70# asphalt and 200# asphalt were heated and melted to 180°C (heating rate 15°C / min). SBS was added, and the mixture was sheared at 183°C and 4000 r / min for 40 min. Then, a crosslinking agent was added, and the mixture was heated to 188°C and stirred at 400 r / min for 10 min (heating rate 5°C / min). Waste tire powder was added and stirred at 188°C and 400 r / min for 1.5 h. Finally, stone powder was added and stirred at 188°C and 400 r / min for 20 min to obtain crosslinked modified asphalt.
[0127] Non-crosslinked modified bitumen coating It is prepared from raw materials including 70# asphalt, 200# asphalt, SBS (791H grade), waste tire powder (60 mesh) and stone powder (200 mesh); the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder is 25:30:2.5:16:26.5.
[0128] The preparation method of the non-crosslinked modified asphalt includes the following steps:
[0129] 70# asphalt and 200# asphalt were heated and melted to 180°C (heating rate of 15°C / min). SBS was added, and the mixture was sheared at 183°C and 4000 r / min for 40 min. Waste tire powder was added, and the mixture was heated to 188°C and stirred at 400 r / min for 1.5 h. Stone powder was then added and stirred at 400 r / min and 188°C for 20 min to obtain non-crosslinked modified asphalt.
[0130] Modified bitumen waterproof membrane The preparation method includes the following steps:
[0131] A cross-linked modified asphalt is coated on the upper surface of the polyester base and cured to obtain a first cross-linked modified asphalt coating with a thickness of 1 mm; a cross-linked modified asphalt is coated on the lower surface of the polyester base and cured to obtain a second cross-linked modified asphalt coating with a thickness of 1 mm; thus obtaining an aging-resistant layer with a thickness of 3 mm.
[0132] Non-crosslinked modified bitumen is coated on one side of the aging-resistant layer. After curing, an adhesive layer with a thickness of 1 mm is obtained, thus obtaining a modified bitumen waterproof membrane.
[0133] The modified bitumen waterproof membrane has a thickness of 4 mm.
[0134] Comparative Example 1
[0135] The difference from Example 1 is as follows:
[0136] Modified bitumen waterproof membrane The preparation method includes the following steps:
[0137] A cross-linked modified asphalt is coated on the upper surface of the polyester base and cured to obtain a first cross-linked modified asphalt coating with a thickness of 1 mm; a cross-linked modified asphalt is coated on the lower surface of the polyester base and cured to obtain a second cross-linked modified asphalt coating with a thickness of 1 mm; thus obtaining an aging-resistant layer with a thickness of 3 mm.
[0138] A cross-linked modified bitumen is coated on one side of the aging-resistant layer. After curing, an adhesive layer with a thickness of 1 mm is obtained, thus obtaining a modified bitumen waterproof membrane.
[0139] Comparative Example 2
[0140] The difference from Example 1 is as follows:
[0141] Modified bitumen waterproof membrane The preparation method includes the following steps:
[0142] A non-crosslinked modified bitumen coating is applied to the upper surface of the polyester base and cured to obtain a first non-crosslinked modified bitumen coating with a thickness of 1 mm; a non-crosslinked modified bitumen coating is applied to the lower surface of the polyester base and cured to obtain a second non-crosslinked modified bitumen coating with a thickness of 1 mm; thus obtaining a conventional modified bitumen roll layer with a thickness of 3 mm.
[0143] Non-crosslinked modified bitumen is coated on one side of the conventional modified bitumen membrane layer. After curing, an adhesive layer with a thickness of 1 mm is obtained, thus obtaining a modified bitumen waterproof membrane.
[0144] The performance of the modified bitumen waterproof membranes prepared in Example 1 and Comparative Examples 1-2 was tested, and the results are shown in Table 1.
[0145] Table 1. Performance data of the modified bitumen waterproof membranes prepared in Example 1 and Comparative Examples 1-2
[0146]
[0147] As shown in Table 1, the modified bitumen waterproof membrane of this invention ensures that the bonding (joint peel strength) of the underlying layer of the membrane is qualified and consistent with that of normal membranes, while avoiding the problem of low bonding peel strength of fully cross-linked membranes (Comparative Example 1). In addition, the chemical cross-linking method improves the heat aging quality loss and low-temperature flexibility performance, and the heat resistance is better than that of non-cross-linked membranes (Comparative Example 2).
[0148] Example 2
[0149] Crosslinking agent include:
[0150] 17 wt% insoluble sulfur
[0151] Super-speed accelerator BZ 8 wt%
[0152] Acceleration accelerator TMTM 10 wt%
[0153] Medium-speed accelerator CZ 9 wt%
[0154] Nano zinc oxide 56 wt%.
[0155] The particle size of the nano zinc oxide is 50~100 nm.
[0156] Rapid crosslinking verification
[0157] The experimental group of asphalt samples: The raw materials used for preparation were 70# asphalt, 200# asphalt, SBS and crosslinking agent; the mass ratio of 70# asphalt, 200# asphalt, SBS and crosslinking agent was 45:55:5:0.2.
[0158] Preparation method: 70# asphalt and 200# asphalt were heated and melted to 180°C (heating rate of 15°C / min). SBS was added, and the mixture was sheared at 183°C for 40 min at 4500 r / min. Then, crosslinking agent was added, and the mixture was heated to 188°C (heating rate of 5°C / min) and stirred at 500 r / min for 1.5 h and 3.5 h. Asphalt samples from the experimental group were taken to observe the crosslinking development.
[0159] Control group asphalt samples: The crosslinking agent in the experimental group asphalt samples was replaced with sulfur, while the remaining raw materials and procedures were the same as those in the experimental group. The crosslinking development was observed in the control group asphalt samples.
[0160] Figure 5 This is a fluorescence microscope image of the crosslinking effect of an asphalt sample developed for 1.5 hours in the experimental group of Example 2 of the present invention.
[0161] Figure 6 This is a fluorescence microscopy crosslinking effect image of an asphalt sample developed for 1.5 hours in the control group of Example 2 of the present invention.
[0162] Figure 7 This is a fluorescence microscopy crosslinking effect image of an asphalt sample developed for 3.5 hours in the control group of Example 2 of the present invention.
[0163] from Figures 5-7 It can be seen that the experimental group obtained by using the crosslinking agent of the present invention can achieve the fluorescent crosslinking state of the control group after 1.5 hours of development.
[0164] Crosslinked modified bitumen coating It is prepared from raw materials including 70# asphalt, 200# asphalt, SBS (791H grade), waste tire powder (60 mesh), stone powder (200 mesh) and the crosslinking agent; the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and crosslinking agent is 26:29:2:17:25.92:0.08.
[0165] The preparation method of the crosslinked modified asphalt includes the following steps:
[0166] 70# asphalt and 200# asphalt were heated and melted to 180°C (heating rate 18°C / min). SBS was added, and the mixture was sheared at 183°C and 4500 r / min for 40 min. Then, a crosslinking agent was added, and the mixture was heated to 188°C and stirred at 500 r / min for 10 min. Waste tire powder was added and stirred at 188°C and 500 r / min for 1.3 h. Finally, stone powder was added and stirred at 188°C and 500 r / min for 0.2 h to obtain crosslinked modified asphalt.
[0167] Non-crosslinked modified bitumen coating It is prepared from raw materials including 70# asphalt, 200# asphalt, SBS (791H grade), waste tire powder (60 mesh) and stone powder (200 mesh); the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder is 26:29:2:17:26.
[0168] The preparation method of the non-crosslinked modified asphalt includes the following steps:
[0169] 70# asphalt and 200# asphalt were heated and melted to 180°C (heating rate 18°C / min). SBS was added, and the mixture was sheared at 183°C and 4500 r / min for 40 min. Waste tire powder was added, and the mixture was heated to 188°C and stirred at 500 r / min for 1.3 h. Stone powder was then added and stirred at 188°C and 500 r / min for 0.2 h to obtain non-crosslinked modified asphalt.
[0170] Modified bitumen waterproof membrane The preparation method includes the following steps:
[0171] A cross-linked modified asphalt coating is applied to the upper surface of the polyester base and cured to obtain a first cross-linked modified asphalt coating with a thickness of 1.25 mm; a cross-linked modified asphalt coating is applied to the lower surface of the polyester base and cured to obtain a second cross-linked modified asphalt coating with a thickness of 1.25 mm; thus obtaining an aging-resistant layer with a thickness of 3.5 mm.
[0172] A non-crosslinked modified bitumen is coated on one side of the aging-resistant layer. After curing, an adhesive layer with a thickness of 0.5 mm is obtained, thus obtaining a modified bitumen waterproof membrane.
[0173] The modified bitumen waterproof membrane has a thickness of 4 mm.
[0174] Comparative Example 3
[0175] The difference from Example 2 is as follows:
[0176] Modified bitumen waterproof membrane The preparation method includes the following steps:
[0177] A cross-linked modified asphalt coating is applied to the upper surface of the polyester base and cured to obtain a first cross-linked modified asphalt coating with a thickness of 1.25 mm; a cross-linked modified asphalt coating is applied to the lower surface of the polyester base and cured to obtain a second cross-linked modified asphalt coating with a thickness of 1.25 mm; thus obtaining an aging-resistant layer with a thickness of 3.5 mm.
[0178] A cross-linked modified bitumen is coated on one side of the aging-resistant layer. After curing, an adhesive layer with a thickness of 0.5 mm is obtained, thus obtaining a modified bitumen waterproof membrane.
[0179] Comparative Example 4
[0180] The difference from Example 2 is as follows:
[0181] Modified bitumen waterproof membrane The preparation method includes the following steps:
[0182] A non-crosslinked modified bitumen coating is applied to the upper surface of a polyester base and cured to obtain a first non-crosslinked modified bitumen coating with a thickness of 1.25 mm; a non-crosslinked modified bitumen coating is applied to the lower surface of the polyester base and cured to obtain a second non-crosslinked modified bitumen coating with a thickness of 1.25 mm; thus obtaining a conventional modified bitumen roll layer with a thickness of 3.5 mm.
[0183] A non-crosslinked modified bitumen is coated on one side of the conventional modified bitumen membrane layer. After curing, an adhesive layer with a thickness of 0.5 mm is obtained, thus obtaining a modified bitumen waterproof membrane.
[0184] The performance of the modified bitumen waterproof membranes prepared in Example 2 and Comparative Examples 3-4 was tested, and the results are shown in Table 2.
[0185] Table 2 Performance data of the modified bitumen waterproof membranes prepared in Example 2 and Comparative Examples 3-4
[0186]
[0187] As shown in Table 2, the modified bitumen waterproof membrane of this invention ensures that the bonding (joint peel strength) of the underlying layer of the membrane is qualified and consistent with that of normal membranes, while avoiding the problem of low bonding peel strength of fully cross-linked membranes (Comparative Example 3). In addition, the chemical cross-linking method improves the heat aging quality loss and low-temperature flexibility performance, and the heat resistance is better than that of non-cross-linked membranes (Comparative Example 4).
[0188] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A modified bitumen waterproofing membrane comprising: an anti-aging layer; a bonding layer formed on the anti-aging layer; the anti-aging layer comprises a polyester base and a cross-linked modified asphalt coating layer formed on an outer surface of the polyester base; the bonding layer is a non-cross-linked modified asphalt coating layer; the cross-linked modified asphalt coating layer is prepared from raw materials comprising 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and a cross-linking agent; the non-cross-linked modified asphalt coating layer is prepared from raw materials comprising 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder.
2. The modified bitumen waterproofing membrane according to claim 1, wherein, the cross-linking agent comprises: insoluble sulfur 15 wt%~25 wt%; ultra-ultra fast accelerator 4 wt%~8 wt%; ultra-fast accelerator 6 wt%~12 wt%; medium speed accelerator 8 wt%~12 wt%; nano zinc oxide 55 wt%~65 wt%; the sum of the amounts of the components is 100%.
3. The modified bitumen waterproofing membrane according to claim 2, wherein, the ultra-ultra fast accelerator is BZ and / or EZ; the ultra-fast accelerator is TMTD and / or TMTM; the medium speed accelerator is at least one of M, DM and CZ; the particle size of the nano zinc oxide is 50~100 nm.
4. The modified bitumen waterproofing membrane of claim 1, wherein, in the preparation raw materials of the cross-linked modified asphalt coating layer, the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder, stone powder and cross-linking agent is 20~35:20~35:1.5~3:12~18:20~35:0.05~0.
15.
5. The modified bitumen waterproofing membrane of claim 1, wherein, the preparation method of the cross-linked modified asphalt comprises the following steps: heat and melt 70# asphalt and 200# asphalt to 175~180℃, add SBS, shear at 3500~4500 r / min and 180~185℃, then add the cross-linking agent, heat to 185~190℃, stir at 300~500 r / min, then add waste tire powder and stir, and finally add stone powder and stir to obtain cross-linked modified asphalt.
6. The modified bitumen waterproofing membrane of claim 1, wherein, the thickness of the anti-aging layer is 2~3.5 mm.
7. The modified bitumen waterproofing membrane of claim 1, wherein, in the preparation raw materials of the non-cross-linked modified asphalt coating layer, the mass ratio of 70# asphalt, 200# asphalt, SBS, waste tire powder and stone powder is 20~35:20~35:1.5~3:12~18:20~35.
8. The modified bitumen waterproofing membrane of claim 1, wherein, the preparation method of the non-cross-linked modified asphalt comprises the following steps: heat and melt 70# asphalt and 200# asphalt to 175~180℃, add SBS, shear at 3500~4500 r / min and 180~185℃, then add waste tire powder, heat to 185~190℃, stir at 300~500 r / min, and finally add stone powder and stir to obtain non-cross-linked modified asphalt.
9. The modified bitumen waterproofing membrane of claim 1, wherein, the thickness of the non-cross-linked modified asphalt layer is 0.5~1 mm; the thickness of the modified asphalt waterproof roll material is 3~4 mm.
10. A preparation method of the modified asphalt waterproof roll material according to claims 1~9, comprising the following steps: coat cross-linked modified asphalt on both sides of the polyester base, and after curing, obtain an anti-aging layer; coat non-cross-linked modified asphalt on one side of the anti-aging layer, and after curing, obtain a bonding layer; thereby obtaining a modified asphalt waterproof roll material.